Pre-co mpetitive overload period impairs parasympathetic modulation in athletes: A systematic review and meta-analysis - Lapo, H. M.; Chacon-Mikahil, M. P. T.; Sardeli, A. V. (Physiology & Behavior, 2022)
Objective The aim was to meta-analyze the effect of different type of overloads on parasympathetic modulation to the heart, assessed by root-mean-square difference of successive normal RR intervals (RMSSD) of athletes.